2008
DOI: 10.1161/atvbaha.108.164210
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren-Binding Increases the Half Life of Renin and Prorenin in Rat Aortic Vascular Smooth Muscle Cells

Abstract: Objective-Renin inhibition with aliskiren has been reported to cause a greater rise in renin than other types of renin-angiotensin system blockade, thereby potentially leading to angiotensin generation or stimulation of the human (pro)renin receptor (h(P)RR). Here we studied whether this rise in renin is attributable to an aliskiren-induced change in the prorenin conformation, allowing its detection in renin assays, or a change in renin/prorenin clearance. We also investigated whether aliskiren affects (pro)re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 24 publications
4
103
0
Order By: Relevance
“…11 It should be noted, however, that at least part of the increase in PRC observed during aliskiren treatment may be the result of an assay artefact related to the ability of aliskiren to bind to and alter the conformation of prorenin, which would then be measured as renin by the standard PRC immunoassay. [27][28][29] This artefact does not occur with ARBs and might account for some of the observed between-treatment differences in PRC. Levels of prorenin were significantly increased from baseline to a similar extent with both irbesartan and aliskiren treatments, an expected consequence of any chronic stimulus of renin release.…”
Section: Discussionmentioning
confidence: 94%
“…11 It should be noted, however, that at least part of the increase in PRC observed during aliskiren treatment may be the result of an assay artefact related to the ability of aliskiren to bind to and alter the conformation of prorenin, which would then be measured as renin by the standard PRC immunoassay. [27][28][29] This artefact does not occur with ARBs and might account for some of the observed between-treatment differences in PRC. Levels of prorenin were significantly increased from baseline to a similar extent with both irbesartan and aliskiren treatments, an expected consequence of any chronic stimulus of renin release.…”
Section: Discussionmentioning
confidence: 94%
“…109 Furthermore, on binding to the (P)RR, prorenin, which is normally inactive, becomes catalytically active (it can cleave Aogen to form Ang I), possibly because of a conformational change induced by the binding. 109,[114][115][116] The Ang IIindependent effects of (P)RR stimulation include activation of extracellular signal-regulated kinase1/2, 109,117,118 and heat shock protein 27 119 and phosphatidylinositol-3 kinase p85a 120 pathways. The production of TGF-b and plasminogen-activator-1 is also increased, as are gene expression and production of collagen I and fibronectin, respectively.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 99%
“…123 In vitro studies showed that when incubated with prorenin, aliskiren binds to the active site of the enzyme 87 and can inhibit Ang I formation that would normally occur from nonproteolytic [(P)RR-mediated] activation of prorenin. 116 This finding is significant because activation of prorenin at tissue sites might occur by (P)RR-mediated mechanisms or by proteolytic cleavage of the prosegment. The latter may occur in tissues in which inflammatory or dead/dying parenchymal cells may release proteases such as cathepsin G or elastase, 124 which are capable of cleaving the prosegment.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…59,63,64 The 34-fold increase might be overestimated because of an assay artefact: by binding to prorenin, aliskiren causes a conformational change in this molecule, which is then detected as (immuno-re)active renin, that is, aliskiren allows the false detection of prorenin as renin. [65][66][67] Nevertheless, renin inhibition can cause a greater increase in plasma renin compared with AT1R blockade at dosages with comparable antihypertensive effects. 68 It has been reported that the plasma renin concentration under 300 mg aliskiren is almost doubled compared with 320 mg valsartan.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%